WHEN GAMIFICATION MEETS AQIDAH AKHLAK: THE ROLE OF BAAMBOOZLE IN STUDENTS’ LEARNING ACHIEVEMENT - Misraturrabiah; Ely Surayya; Edi Saputra (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aimed to investigate the effectiveness of Baamboozle, a gamification-based learning platform, in improving students’ learning achievement in Aqidah Akhlak, particularly on the topics of honesty and responsibility. The study employed Classroom Action Research based on the Kemmis and McTaggart model, involving planning, action, observation, and reflection stages conducted over two cycles. The participants were 28 seventh-grade students at Madrasah Tsanawiyah Nurul Yaqin, Indonesia. Data were collected through classroom observations, learning achievement tests, questionnaires, and documentation, then analyzed using descriptive quantitative and qualitative techniques. The findings showed a consistent improvement in students’ learning achievement after the implementation of Baamboozle. The mean score increased from 65 in the pre-cycle stage to 74 in Cycle I and 86 in Cycle II. The learning mastery rate also improved from 40% to 68% and finally reached 89%. Classroom observations further indicated that students became more active, engaged, collaborative, and willing to participate in discussions and learning activities. These results suggest that Baamboozle-assisted gamification created a more interactive and student-centered learning environment. The study implies that gamification can be an effective pedagogical strategy for improving learning achievement and classroom engagement in Aqidah Akhlak instruction. It also highlights that successful digital gamification requires careful instructional planning, clear guidance, and effective classroom management. This study contributes to the limited empirical literature on gamification in Islamic education by examining Baamboozle in Aqidah Akhlak instruction within a Madrasah Tsanawiyah context. Unlike studies focusing mainly on motivation, perception, or technology acceptance, this study provides classroom-based evidence of improved measurable achievement, participation, and engagement in Islamic moral education.